Trends in the Regulation of Hate Speech and Fake News: A Threat to Free Speech? - Santuraki, Suleiman Usman (Faculty of Law, Hasanuddin University, 2019)
The Information and Communication Technology (ICT) revolution heralding the emergence and dominance of social media has always been viewed as a turning point in free speech and communication. Indeed, the social media ordinarily represents the freedom of all people to speech and information. But then, there is also the side of the social media that has been often ignored; that it serves as platform for all and sundry to express themselves with little, if any regulation or legal consequences. This as a result has led to global explosion of hate speech and fake news. Hate speech normally lead to tension and holds in it, the potential for national or even international crisis of untold proportions. It also has the likelihood to scare people away from expressing themselves for fear of hate-filled responses and becoming a source of fake news. Using doctrinal as well as comparative methodologies, this paper appraises the trend between states of passing laws or proposing laws to regulate hate speech and fake news; it also appraises the contents of such laws from different countries with the aim of identifying how they may be used to suppress free speech under the guise of regulating hate speech and fake news. It argues that the alarming trend of hate speech and fake news presented an opportunity for leaders across the globe to curb free speech. The paper concludes that the advancement in ICT helped in a great deal to advance free speech; it may as well, because of the spread of hate speech and fake news, lead to a reverse of that success story.